Endovascular flow diversion for treatment of anterior communicating artery region cerebral aneurysms: a single-center cohort of 50 cases. (27th January 2017) - Colby, Geoffrey P; Bender, Matthew T; Lin, Li-Mei; Beaty, Narlin; Huang, Judy; Tamargo, Rafael J; Coon, Alexander L
Abstract : Background: Flow diversion represents a novel but definitive treatment for recurrent and difficult-to-coil aneurysms of the anterior communicating artery (ACoA) region, of which reports are limited. Objective: To determine the effectiveness of the Pipeline embolization device (PED) in treating aneurysms in the ACoA region. Methods: We retrospectively reviewed an IRB-approved database of patients with an aneurysm at a single institution for patients with ACoA or A1–A2 aneurysms treated with PED. Data analyzed included demographics, aneurysm characteristics, procedural details, follow-up results, and outcomes. Results: A total of 50 procedures were performed on 41 patients, including seven patients who underwent bilateral 'H-pipe' PED placement. The average age was 56 years and 46% of the patients were female. The average aneurysm size was 4.5 mm, and two large (>10 mm) aneurysms were treated. The vessel of origin was either the ACoA (26 aneurysms, 63%) or the A1–A2 junction (15 aneurysms, 37%). Eighteen patients (44%) had prior subarachnoid hemorrhage and 20 had previously been treated either with clipping (6 aneurysms, 15%) or coiling (14 aneurysms, 34%). Procedural success was achieved in 48/50 cases (96%) and two cases were aborted. Coils were deployed adjunctively in two cases (4%). Procedural outcomes included no deaths, one major ischemic stroke (2%), and two patients with intracranial hemorrhage (4%). Complete aneurysm occlusion was achieved in 81% of patients at 6 months and 85% of patients at last follow-up digital subtraction angiography. Conclusions: The PED can be used safely and effectively in the treatment of aneurysms of the ACoA region. This represents a good alternative treatment option to microsurgical clipping and endovascular coiling.